How strong is enemy release? A systematic compilation across taxa and approaches - Karen Zeng; Jessica Schembri; Eve Slavich; Angela T. Moles (Ecology, 2026)
The enemy release hypothesis posits that introduced species escape some of their predators, pathogens, and parasites when they move to a new range. We used a systematic review to compile data from 691 contrasts of enemy release spanning plants, animals, and algae in aquatic and terrestrial systems worldwide. Data from 311 biogeographic contrasts (between home and new range) revealed that on average, a species experiences only 43% as much enemy pressure in their introduced range as they experience in their native range. Data from 380 community contrasts (between native and introduced species) revealed that introduced species experience on average 70% of the enemy pressure that their native congeners endure. Interestingly, one third (36%) of contrasts showed higher, rather than lower, enemy pressure on the introduced population. Enemy release was well supported in contrasts of the diversity of enemies and enemy damage but not significant in contrasts of host fitness, suggesting that while introduced populations are attacked by fewer enemies, this does not always result in higher fitness. We also found that biogeographic enemy release was higher in mollusks and fish but lower in insects and algae, indicating that certain taxa may be favored by enemy release. We hope that an improved understanding of the extent to which introduced species are released from enemy pressures will help managers to identify good opportunities for biocontrol and to understand the factors likely to be affecting the success of invasive species.